Perlindungan Hukum Pemegang Hak Merek Terkenal Terhadap Penjualan Barang Palsu Merek Soffell Lotion : Studi Putusan Mahkamah Agung Nomor: 503 K/PID.SUS/2016 - Agung Firmansyah; OK Saidin; Tengku Keizerina Devi; Jelly Leviza (Universitas Sumatera Utara, 2019)
Abstract. Brand is part of the form of intellectual work, in the trade of goods /services, the brand is the identity of a company that has an important role for the smooth and increased trade in goods / services. In a trade, there is a competition, where greater trade competition can encourage other people to trade by falsifying goods on a brand, especially a well-known brand that results in losses for the brand owner. Lack of supervision and enforcement of counterfeiting of brands in Indonesia has resulted in a lot of circulation of counterfeit goods. Therefore, the government is expected to be more assertive in overseeing the circulation of counterfeit goods, especially the Soffell Lotion brand, and to take firm action against counterfeiters who do not have good intentions, so that justice is created in the middle of society. This type of research is normative legal research, where the approach towards the problem is carried out by reviewing the applicable laws and regulations according the agreements and other legal materials . The nature of this research is descriptive analyst because this research will reveal the facts and analyze the legal phenomena that exist nowadays. This research analysis uses the deductive method to draw conclusions from the general to the specific. That is the way of thinking in general conclusions based on specific facts. Legal protection against a well-known brand needs to be done, because an act done intentionally and without rights by using the same brand in its entirety with another party's registered brand for similar goods or services that are produced and / or traded is a trademark violation. In national law, the protection of a well-known brand is regulated in Article 21 paragraph (1) of the Brand Law and Geographical indications, and the protection of a well-known mark according to international law can be seen from the Paris Convention and TRIPS Agreement which requires that member countries to protect a well-known Brands. In determining the fame of a brand, it can be seen in Article 21 paragraph (1) letter b of Law Number 20 Year 2016 concerning Brand and Geographical Indications, which is based on the general public's knowledge, promotion and marketing on a large scale, as well as Investments in several countries in the world which is carried out by the owner and accompanied by proof of registration of the brand in several countries. Keywords: counterfeiting, protection, famous brand